Novel non-curable resection prediction model for early colorectal cancer following endoscopic submucosal dissection based on inflammatory immune index - Li, Xiunan; Zhang, Lei; Xu, Biao; Ding, Shu; Wang, Jing; Jia, Yu (Frontiers in Medicine, 2025)
BackgroundsColorectal carcinoma represents one of the common malignant tumors of digestive tract in clinic. Systemic immune inflammation index (SII) has great potential in predicting prognosis of digestive tract tumors. We sought to explore the predictive ability of SII for non-curative resection of early colorectal cancer treated with ESD, and to establish a related predictive model.MethodsA retrospective analysis was performed on data from patients with early-stage colorectal cancer who underwent ESD in our hospital between January 2019 and December 2022. To establish the optimal cut-off value for the SII, Receiver Operating Characteristic (ROC) curves were generated, correlating preoperative SII levels with postoperative resection outcomes. Patients were categorized into high SII and low SII groups, and their clinical characteristics were comparatively analyzed. Furthermore, patients were stratified according to the presence or absence of non-curative resection outcomes post-ESD, to identify independent risk factors associated with non-curative resection. A prognostic nomogram was subsequently developed to enhance predictive accuracy for non-curative resection, integrating identified risk variables.ResultsA total of 215 patients were enrolled in this study, all of whom successfully underwent ESD, achieving an en bloc resection rate of 96.7%. Based on surgical procedures and pathological resection characteristics, 181 cases were classified as curative resections, whereas 34 cases of non-curative resections. Postoperative complications occurred in 10 patients, resulting in a complication rate of 4.7%. The optimal cut-off value of SII was 629.2 × 10∧9/L (area under the curve: 0.762, P < 0.001), and the sensitivity and specificity was 64.7 and 85.6%, respectively. An optimal SII cut-off value for predicting non-curative resection was determined to be 1.56 (AUC: 0.571, 95% CI: 0.501–0.641). Multivariate analysis demonstrated that elevated SII (P = 0.002), a positive lifting sign (P = 0.003), increased tumor size (P = 0.034), and poor tumor differentiation (P < 0.001) were independent risk factors significantly associated with non-curative resection.ConclusionSII revealed well correlation in predicting non-curable resection in patients with early colorectal cancer treated by ESD. Meanwhile, the higher the patient’s NLR, PLR, tumor diameter and infiltration depth, the more likely to occur postoperative non-curative resection.